Exploring the entrepreneurial and innovative climate: Academic Librarians' perspective / Haziah Sa'ari ... [et al.] - Sa'ari, Haziah; Mohamed, Al Bakri; Mohd Tahir, Mohd Roslan; Abd Wahab, Siti Aishah; Syed Noh, Sharifah Nazura (2018)
To respond to a demand of fostering entrepreneurial and service innovativeness as competitive outcomes in their work place, academic librarians need to work in a supportive organizational climate. As an enabler to motivate the creativity of academic librarians toward recognizing a problem and finding its solution, organizational climate interacts along with entrepreneurial competencies to transform them into a new working process as opposed to the traditional professional parameters of librarians. The objective of this paper seeks to explore the motivational factor of organizational climate leading to innovative behavior among academic librarians. A comparative case study was conducted at two academic libraries in Malaysian research universities. The data was obtained by using focus group discussions with 12 informants. In order to accomplish the qualitative data analysis, the themes found which confined the antecedents of environmental factors (research focus center/greater graduate education/more funding options), rewards (recognition and performance measurement) and work group (team and composition). The domains revealed by the findings are the contextual factors both internal and external organizational climate influenced the librarians to practice their entrepreneurial and innovative behavior directed towards a common objective to both cases which is fulfilling the mission and continuing maintenance of the goals of the position of the two universities in the world ranking status.